2010
DOI: 10.3113/fai.2010.0695
|View full text |Cite
|
Sign up to set email alerts
|

Novel Reconstruction of a Static Medial Ligamentous Complex in a Flatfoot Model

Abstract: The surgical technique evaluated here may be useful as a new soft tissue reconstructive procedure for treating adult flatfoot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…We found that reconstructing the soft tissues of the medial arch (Figures 1B and 1C) provide excellent correction of the midfoot deformity, which agrees with previous investigations by Choi et al 6 and Tan et al 27 Furthermore, tibio-navicular reconstruction corrected the midfoot eversion deformity, which compares similarly to a reconstruction of the of the deltoid complex. 19 There was a graded effect between deformity correction and proximal fixation of the reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…We found that reconstructing the soft tissues of the medial arch (Figures 1B and 1C) provide excellent correction of the midfoot deformity, which agrees with previous investigations by Choi et al 6 and Tan et al 27 Furthermore, tibio-navicular reconstruction corrected the midfoot eversion deformity, which compares similarly to a reconstruction of the of the deltoid complex. 19 There was a graded effect between deformity correction and proximal fixation of the reconstruction.…”
Section: Discussionsupporting
confidence: 90%
“…1,4,5,8 Lateral column lengthening and fusions do not re-create normal foot kinematics, and many report reduced subjective and objective outcomes. 1,11,15,20,23,[34][35][36] Complication rates are higher 16,18,25,27,32,[39][40][41][42][43][44][45][46][47][48][49] and carry additional risks to joint-preserving procedures such as nonunion, avascular necrosis, and increased incidence of secondary arthritis. 33,34,42 Subsequently, joint preservation surgery has become increasingly explored.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used was a modification of a method using semitendinosus allograft. 21,40 The patient was positioned supine with an above-knee tourniquet. If required, a medial head of gastrocnemius recession and medializing calcaneal osteotomy were performed.…”
Section: Tendon Allograft Operative Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of a flexible deformity, as the medial column is corrected and stabilized, the lateral column is "pulled" distally by the correction (Figure 3). Stabilization of the N-C joint can be performed with an arthrodesis or, as biomechanically demonstrated by Tan and Kadakia et al, 4 a medial ligamentous reconstruction can be performed. This allows correction of the deformity without the need for an arthrodesis (Figure 4).…”
mentioning
confidence: 99%